EXPLORING THE NEXUS OF CONFLICT MANAGEMENT AND ORGANIZATIONAL PERFORMANCE: INSIGHTS OF EFFECTIVE WORKPLACE DYNAMICS - Olalekan Eezekiel Ajayi (International Relations Study Program of Universitas Kristen Indonesia (UKI), 2025)
This research examines the complex link between conflict management, organizational performance, and successful workplace dynamics. Conflict within businesses is unavoidable; nonetheless, how it is handled has a substantial influence on overall performance and the quality of workplace relationships. Drawing from relevant literature and theoretical frameworks, this study investigates many aspects of conflict management methods and their consequences for organizational performance. The investigation begins by explaining the importance of conflict resolution in the context of organizational performance. It emphasizes the negative impact of unresolved disagreements on increased productivity, employee morale, and company culture. It emphasizes the need to foster open communication lines, develop clear dispute-resolution procedures, and nurture a culture of respect and empathy. The study underscores the importance of leadership in setting the tone for conflict resolution, highlighting managers' need to serve as facilitators of constructive discourse and advocates for corporate values. Conflict management affects organizational performance measures such as collaboration, competing, Competing, avoiding, and accommodation. It demonstrates the link between successful conflict management and Organizational Performance in the workplace and its impact on increased team cohesiveness, innovation, and flexibility. Organizations can achieve long-term success by reducing interpersonal conflict and fostering a supportive work environment. this study calls for comprehensive knowledge of conflict management as an essential component of workplace effectiveness. Organizations may successfully traverse hurdles and prosper in today's changing business world by using proactive conflict management solutions based on empathy, teamwork, and shared purpose